Analisis Pekerja Pada Industri Konveksi Di Kecamatan Polokarto Kabupaten Sukoharjo - Sulistyani, Wahyu; Dra. Umrotun, M.Si, Drs. Priyono, M.Si (2016)
Span the year 2007-2015 amount of small convection industry and labour in Polokarto District experience of the increasing. Amount of convection industry experience of the increasing equal to 80,95% and labour equal to 82,38%. Existence of the make-up of the amount of industry and indication labour that industry affect positive at social, society economic condition. The aims of this research was (1) analysing demography characteristic, social, worker economics convection industrial, (2) analysing industrial worker room, (3) analysing factors pushing to put hand to the convection industry, and (4) analysing the level of industrial labor fringe benefit contribution of convection to family total earnings. Method used in this research was method survey. The data analysis was using frequency tables analysis and crossed tables analyse. Respondents in this research was industrial worker of convection summed uply counted 101 respondents. Result got from this research was (1) demography respondents characteristic (social and economic) have variety. As for its character shall be as follows: all industrial worker of convection in Polokarto District have old age productive (15-64 year), mostly industrial worker of convection in Polokarto District have a woman, maried status, owning the amount of family member was namely gyrate 4 - 5 people, owning the amount of family responsibility was namely gyrate 2-3 people, owning low education level, owning especial work in convection industry, owning small effort llama, owning small office hours, owning travelled distance which was closed to workplace, owning small earnings (Rp. 320.000 - Rp. 1.046.667); (2) most coming from respondents have the group pattern and come from within Polokarto District, namely equal to 99 respondents or 99% from totalizeing 101 respondents and the rest or 2 respondents come from outside Polokarto District (Mojolaban District); (3) pushing worker work factor in convection industry among others was get the high salary, namely equal to 5% respondents, free or unattached office hours namely equal to 27% respondents, getting health guarantee namely equal to 12% respondents, there was no tying contract namely equal to 23% respondents, near by from residence namely equal to 32% respondents, and work which do not too heavy, so that make balmy of worker namely equal to 2% respondents; and (4) mostly contribution of labor fringe benefit to total earnings of high family namely equal to 42 respondents (41,60%) and have the contribution between > 70,9 - 100%.